Molecular detection of Ehrlichia canis and Ehrlichia ewingii coinfection in a dog in Ecuador - Chalco-Torres, Lorena Elizabeth (2023)
The study of a dog with symptoms of Parvovirus that was positive in immunochromatography tests for Parvovirus and Ehrlichia canis and that was confirmed by PCR as positive for E. canis and E. ewingii was presented. In addition to the interest that this case represents from the clinical point of view, the molecular detection of E. ewingii suggests the presence of this pathogen outside its natural geographic distribution range (Mexico, Guatemala, Guyana, French Guiana, and the United States). Also, it highlights the possibility of conducting molecular studies in local ticks to verify if this was an isolated case in Ecuador or if there was a colonization of E. ewingii in local vectors.